Iron and Virulence in Francisella tularensis - Ramakrishnan, Girija (Frontiers in Cellular and Infection Microbiology, 2017)
Francisella tularensis, the causative agent of tularemia, is a Gram-negative bacterium that infects a variety of cell types including macrophages, and propagates with great efficiency in the cytoplasm. Iron, essential for key enzymatic and redox reactions, is among the nutrients required to support this pathogenic lifestyle and the bacterium relies on specialized mechanisms to acquire iron within the host environment. Two distinct pathways for iron acquisition are encoded by the F. tularensis genome- a siderophore-dependent ferric iron uptake system and a ferrous iron transport system. Genes of the Fur-regulated fslABCDEF operon direct the production and transport of the siderophore rhizoferrin. Siderophore biosynthesis involves enzymes FslA and FslC, while export across the inner membrane is mediated by FslB. Uptake of the rhizoferrin- ferric iron complex is effected by the siderophore receptor FslE in the outer membrane in a TonB-independent process, and FslD is responsible for uptake across the inner membrane. Ferrous iron uptake relies largely on high affinity transport by FupA in the outer membrane, while the Fur-regulated FeoB protein mediates transport across the inner membrane. FslE and FupA are paralogous proteins, sharing sequence similarity and possibly sharing structural features as well. This review summarizes current knowledge of iron acquisition in this organism and the critical role of these uptake systems in bacterial pathogenicity.